(untitled) (LACCEI, 2024)
The textile industry in Peru is one of the most representative in terms of its contribution to GDP however, in the last 10 years the industry has suffered a 1.5% annual drop in its share of GDP. This is due to the fact that the sector suffers from a series of deficiencies such as low productive efficiency, which is 70.2%. Faced with this problem, some authors opted for the application of some tools such as SMED, SW and 5s to counteract it. But according to the literature review, there is a lack of knowledge of the application of the mentioned tools in textile SMEs, since SMED and 5s are mostly applied in large companies, while SW has little history of applicability despite being a powerful tool that achieves positive changes in production. Therefore, in order to provide a solution to the problem studied, it is necessary to apply the aforementioned tools. This article proposes an improvement model that aims to increase the efficiency of a textile SME through the applicability of tools such as 5S, SMED and SW. The effectiveness of the model was validated with the use of the simulation developed in arena software, obtaining as main result that the efficiency of the sewing area in the textile SME increased from 64.5% to 80%. This leads to the conclusion that the proposal manages to improve the company’s productivity, which allows it to generate higher income by making efficient use of its resources.